PENGARUH KEPUASAN DAN SWICHING COST TERHADAP LOYALITAS PENGGUNA JASA TIKI DI KOTA PADANG - Nofita, Yulia; Amaluis, Dina; Rheza Syahrul, Alfatthory (Pendidikan Ekonomi, 2014)
Dina Amaluis[1], Alfatthory Rheza Syahrul[2]ABSTRACTThis study was conducted to determine the effect of satisfaction on loyalty and cost swiching users TIKI Padang . The population in this study is the city of Padang TIKI customer service is still active until 2013 with a total sample of 100 respondents . The sampling technique used is accidental sampling. Based on the results of the hypothesis test is carried out partially can be seen that the satisfaction and cost swiching has a positive and significant influence on user loyalty TIKI Padang where significant levels < 0.05 alpha . Then simultaneously and swiching cos satisfaction has a positive and significant influence on user loyalty TIKI Padang with the calculated F value significant at 43.381 and 0.000 < 0.05 . From the research , it was found that satisfaction and cost swiching only 77.3 % had an influence on user loyalty TIKI Padang , while 22.3 % is determined by factors other than satisfaction and cost swiching in this study . This result is known from the R Square value of 0.773 ( 77.3 % ).